Experimental study on the behaviour of masonry pavilion vaults on spreading supports. (August 2017) - Rossi, M.; Calvo Barentin, C.; Van Mele, T.; Block, P.
Abstract: Over the years, historic unreinforced masonry vaults have been proved to be particularly vulnerable to dynamic actions and large displacements. This paper focuses on the investigation of the structural behaviour of a pavilion vault on spreading supports by means of experimental tests on a 3D–printed scale model made of discrete blocks. Both the collapse mechanisms and the ultimate displacement capacity are analysed. The reliability of this method for investigating the collapse of vaulted structures is validated by drawing analogies with crack patterns of real vaults. The experimental data are compared with the results obtained by thrust line analysis. A good prediction is obtained by making specific assumptions that take into account three-dimensional effects, which demonstrates the importance of thrust line analysis also for 3D collapse.